Clinical and Radiographic Evaluation of Adult Spinal Deformity. Issue 1 (February 2016) - Bess, Shay; Protopsaltis, Themistocles S.; Lafage, Virginie; Lafage, Renaud; Ames, Christopher P.; Errico, Thomas; Smith, Justin S.
Abstract : Adult spinal deformity (ASD) is a complex disease comprised of different deformity types that often involve the entire spine. Accurate assessment of ASD requires a thorough radiographic evaluation of both the spine and pelvis, including concomitant assessment of the cervical, thoracic, and lumbar spine, as well as the femoral heads and pelvis. Radiographic measurements should include assessment of regional alignment (including lumbar lordosis, thoracic kyphosis, C2–C7 lordosis), global alignment (including C7 SVA, C2–C7 SVA, and T1 pelvic angle), and measures of pelvic compensation and morphology (pelvic tilt, pelvic incidence, T1 slope, and C2-pelvic tilt). Together these radiographic parameters provide important information regarding how the ASD patient maintains upright posture and correlate with the patient's pain and disability. ASD surgical planning must integrate regional, global, and pelvic compensatory/morphologic parameters to adequately correct deformity and thereby provide pain relief and improve function. Radiographic classifications for cervical and thoracolumbar deformities have been developed that utilize the regional and global measures of spinal deformity that are most predictive of patient-reported pain and function. These classifications are aimed to standardize the assessment of ASD to aid in clinical management and to facilitate future research on the evaluation and treatment of ASD.